Calculating sediment trapping efficiencies for reservoirs in tropical settings: A case study from the Burdekin Falls Dam, NE Australia. Issue 2 (25th February 2013) - Lewis, Stephen E.; Bainbridge, Zoë T.; Kuhnert, Petra M.; Sherman, Bradford S.; Henderson, Brent; Dougall, Cameron; Cooper, Michelle; Brodie, Jon E.
Key Points Brune and Churchill curves poorly predict reservoir trapping in tropical rivers A modification to the Churchill curve shows promise to better predict trapping The partitioning of particle size fractions through reservoirs are highlighted